Work-life balance mediating stress and quality of life in academics during COVID-19 in Malaysia - Lwin M. Aye; Jeremy Ern Hwei Tan; Shamala Ramasamy (AOSIS, 2024)
Background: Following the implementation of the Movement Control Order (MCO) during the coronavirus disease 2019 (COVID-19) pandemic, academicians from the universities in Malaysia needed to ensure that the quality-of-service delivery to the stakeholders is undisturbed by adopting new challenging norms. This compromises the work-life balance (WLB), causes more stress and potentially affects their quality of life (QoL). Aim: This study investigates how perceived stress (PS) impacts the QoL of Malaysian academicians during the COVID-19 pandemic, focusing on the mediating role of WLB. Setting: Academics working in Malaysia during COVID-19 pandemic. Methods: A cross-sectional study, using a voluntary response sampling method, was conducted among 417 academicians from universities in Malaysia in September 2021. A self-reported online questionnaire, measuring PS, WLB and QoL, was distributed. Results: The QoL scored a mean of 50 (standard deviation [s.d.] = 9.84), PS scored a mean of 24.26 (s.d. = 8.19) and WLB had a mean score of 51.12 (s.d. = 18.73). Work-life balance was a significant mediator of PS and QoL (β = -0.43, 95% confidence interval [CI] = -0.52 to -0.35, p = 0.0001). Perceived stress was a significant predictor of WLB (β = 1.62, p = 0.0001). Conclusion: Institutions should consider implementing flexible working arrangements, and providing workshops on crisis management, time management, and resilience. Stress coping methods are recommended for enhancing WLB among academicians. Contribution: This study contributes to the pool of evidence to support intervention strategies and policy recommendations aimed to enhance well-being.